2020
DOI: 10.36899/japs.2020.3.0065
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Live Body Weight Using Body Measurements for Jawa Brebes (Jabres) Cattle

Abstract: Bodyweight estimation is important for any aspect of livestock management. Jabres cattle farmers use bodyweight estimation to determine the cattle price in the traditional market. Nowadays, they only use eye-based assessment to predict cattle body weight with a lot of inaccuracies. In this study, the cattle body weight was estimated based on body size measurements data, namely body length, heart girth, withers height, rump height, face length, and face width. The data were collected from Jabres cattle reared i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Jakaria et al (2019) stated that to date, cattle weight in traditional trading practice relies on estimation by traders without using scale. Haq et al (2020) added that in Brebes District, Central Java, the Jabres cattle farmers estimated and predicted the BW of their cattle only by eyebased assessment or called "jogrog" method for determining the cattle price. The inaccuracy in predicting body weight lowers the bargaining position of the smallholder farmers so that profits are not optimal.…”
Section: Regression Models Between Body Measurements and Body Weightmentioning
confidence: 99%
See 1 more Smart Citation
“…Jakaria et al (2019) stated that to date, cattle weight in traditional trading practice relies on estimation by traders without using scale. Haq et al (2020) added that in Brebes District, Central Java, the Jabres cattle farmers estimated and predicted the BW of their cattle only by eyebased assessment or called "jogrog" method for determining the cattle price. The inaccuracy in predicting body weight lowers the bargaining position of the smallholder farmers so that profits are not optimal.…”
Section: Regression Models Between Body Measurements and Body Weightmentioning
confidence: 99%
“…This study indicated that CG is the best and most accurate single predictor of BW for Batur sheep. As well as to other local Indonesian cattle such as Ongole Crossbred cattle (Paputungan et al 2013), Aceh cattle (Putra et al 2014), Simental-Ongole Crossbred cattle (Suliani et al 2017), Bali cattle (Jakaria et al 2019), Jabres cows (Haq et al 2020), Etawah Peranakan goats (Dahklan et al 2020), Kacang goats (Depison et al 2020), Saburai goats (Dakhlan et al 2021). For the breeding purpose or evaluation of growth and productivity performance can use a more precise model with a combination of several variables (Taye et al 2016).…”
Section: Regression Models Between Body Measurements and Body Weightmentioning
confidence: 99%
“…So far, the weight of livestock in traditional trading practices in Indonesia still relies on traders' estimates without using scales (Jakaria et al 2019). Meanwhile, in Brebes District, Central Java, smallholder farmers transacting in the animal market will estimate and predict the BW of their livestock only by eye assessment, generally known as "jogrog" which will then determine the selling price of the livestock (Haq et al 2020). The results of the prediction of "jogrog" will certainly have an uncertain accuracy value because it is only based on the experience and skills of each.…”
Section: Regression Model Between Body Size and Body Weightmentioning
confidence: 99%
“…In commu-nal areas, where there is a lack of resources, predicting body weight from biometric traits is the easiest and affordable procedure that may greatly assist prediction (Hlokoe and Tyasi, 2021). Body weight is an economic significant trait in livestock, and it assists greatly during farm management when feeding, vaccinating, marketing animals and when measuring growth performance (Haq et al, 2020), while biometric traits play a significant role in the prediction of body weight during breeding (Yakubu et al, 2015;Tyasi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%